Typical Characteristics of Agung Banana (Musa paradisiaca) from Lumajang - Rakhmawati, Yunita; Rahayu Lestari, Sri (KnE Life Sciences, 2021)
Banana is a superior commodity in Indonesia, and its growth is unaffected by seasons. Lumajang districts are one of the significant regions of East Java known for producing bananas, particularly the Tanduk banana (Musa paradisiaca) which are also known as the agung banana. The aim of this study was to characterize agung banana as one of the M. paradisiaca cultivars. The present study was conducted between May and June 2020 in Pasrujambe sub-district. The results showed that agung banana is typically shaped like a horn and is 32 cm in length and 16 cm in diameter. Each bunch of agung banana has about 1–2 hands. Every hand has 15–20 fingers and weighs around 20–30 kg per bunch. Agung banana has a thick pulp and is sweet and yellow in colour. The colour of rind changes to black after about two weeks, and although it might look like a rotten fruit, the pulp remains hard and tastes sweeter. Each cluster has about 2–3 suckers. The fruit is generally ready for harvest after 11 months of plantation and can hold on for up to three weeks. Keywords: characterization, banana, Musa paradisiaca, Lumajang